Study of the Seismic Resistance of the Underground Spherical Shell - Zhabbarova X.K (Genius Journals, 2022)
The article presents the calculation of the subsurface structures of the spherical shell type using the seismodynamic theory. The results of the calculation were presented and compared with the results obtained in the classical form
Keywords: construction; dynamic theory of seismic resistance; coefficients; oscillations